AB0171 Anti-carbamylated protein antibodies in patients with systemic sclerosis: an intriguing association with skin involvement. (15th June 2017) - Favoino, E; Prete, M; Vettori, S; Corrado, A; Cantatore, FP; Valentini, G; Perosa, F
Abstract : Background: Systemic sclerosis (SSc), one of the most complex connective tissue disease, is characterized by three pathogenic events namely, vascular damage, autoimmunity and fibroblast activation, leading to a widespread fibrosis of skin and internal organs (1, 2). Previous studies showed that 1) carbamylation mainly affects structural proteins undergoing to a low turn-over rate, namely dermal skin and tendons-associated proteins; and that 2) carbamylated proteins accumulate in skin in an age-dependent manner, contributing to tissue alteration (3). Objectives: As dermis is a disease target and anti-carbamylated protein antibodies (anti-CarP Ab) have been reported in patients with SSc (4), we sought to evaluate any relationship between anti-CarP Ab and clinical parameters reflecting skin involvement in SSc. Methods: Serum samples and clinical data from 123 patients with SSc were collected. Anti-CarP Ab were detected by indirect ELISA, using carbamylated bovine serum albumin as the antigen. Serum Anti-CarP Ab levels were also measured in 41 healthy aged-matched individuals. Clinical data were retrieved as previously reported (5). Results: The mean serum levels of anti-CarP Ab did not statistically differ between healthy and SSc group. In SSc, Spearman analysis showed that anti-CarP inversely correlated with the modified Rodnan skin score (RSS) ( R = -0.325, p<0.001), independently of patients' age. Receiver operating characteristics (ROC) analysis identified the anti-CarP cutoff that best discriminated dichotomized clinical variables related to skin involvement. This cutoff that was employed to subdivide SSc patients into anti-CarP positive and anti-CarP negative patients. Three SSc skin-related clinical parameters were significantly different between groups: RSS (p=0.001), SI skin (p=0.002), and scleredema (p<0.001). A worse skin involvement was associated with low anti-CarP levels. Conclusions: The study shows that anti-CarP Ab serum level inversely associates to the severity of skin involvement in SSc patients. One possible mechanism to explain the inverse association is that the disease-dependent accumulation of carbamylated proteins in the skin may neutralize circulating anti-CarP Ab, thus contributing to their serum levels decrease. However, further investigation is needed to clarify this issue and to assess whether the levels anti-CarP Ab can be useful in the clinical setting of SSc. References: Varga J, Abraham D. J Clin Invest 117:557–67, 2007. Guy S, Kong J, Cheema GS, Keen CL, Wick G, Gershwin ME. Semin Arthritis Rheum 38:132–60, 2008. Gorisse L, Pietrement C, Vuiblet V, Schmelzer CEH, Köhler M, Duca L, Debelle L, Fornès P, S Jaisson, and Gillery P. Proc Natl Acad Sci U S A 113(5): 1191–1196, 2016. Pecani A, Alessandri C, Spinelli FR, Priori R, Riccieri V, Di Franco M, Ceccarelli F, Colasanti T, Pendolino M, Mancini R, Truglia S, Barbati C, Vomero M, Sabatinelli D, Morello F, Valesini G, Conti F. Arthritis Res Ther 18(1):276, 2016. Perosa F, Favoino E, Favia IE, Vettori S, Prete M, Corrado A, Cantatore FP, Valentini G. Medicine (Baltimore) 95(25), 2016. Disclosure of Interest: None declared